Monolithic Germanium-tin pedestal waveguide for mid-infrared applications - Goh, Simon Chun Kiat (2021)
Germanium-tin (GeSn) is a CMOS-compatible group-IV material. Its growth, however, is plagued by the tendency of Sn segregation and the generation of defects within the GeSn layer when it is grown on the lattice-mismatched substrate. Thus far, thin GeSn has been reported for use in a direct-band gap for near-mid infrared light source and photodetector. In this communication, we report the growth of high quality single-crystalline GeSn (∼ 1 μm) with low compressive stress (−0.3%) and low defects (3 × 10 7 /cm 2 ) on Ge buffer on Si substrate. The as-grown GeSn is then fabricated into pedestal waveguide of width 1.25 μm. An estimated propagation loss of 1.81 dB/cm and bending loss of 0.19 dB/ bend are measured at 3.74 μm. In the absence of Ge-O absorption peaks at 820 and 550 cm −1 , under optimal fabrication and measurement condition, the proposed GeSn waveguide might possibly support light propagation for wavelength beyond 25 μm.